Collaborative Governance dalam Pengembangan Desa Wisata Gubugklakah Kabupaten Malang - Akbar, Robeth; Supriyono, Bambang; Domai, Tjahjanulin (Jurnal Ilmiah Administrasi Publik, 2022)
Collaborative Governance, collaboration is the answer to the complexity of the problems that need to be addressed by the government. The collaborative approach can also be applied in tourism development. One of them is the practice of collaboration in Gubugklakah Village. This collaboration was initiated by the people of Gubugklakah Village with the aim of adding economic values to the community. This research is a descriptive study with a qualitative approach, so that the types of data obtained are primary data from in-depth interviews and secondary data. Based on the research conducted, it was found that the collaboration process starts from face-to-face dialogue or intensive communication between actors. In addition, the starting conditions, institutional design, and facilitative leadership factors are supporting factors in collaboration in the development of the Gubugklakah Tourism Village.